Productive and reproductive performance of crossbred and indigenous Dairy cows under rural conditions in Comilla, Bangladesh (University Journal of Zoology, Rajshahi University, 2008)
A comparative account of the productive and reproductive performance of crossbred and indigenous dairy cows at some selected areas of Comilla district. The survey was conducted on 50 dairy cows for a period of four months from June to September, 2004. Out of 50 cows 25 were crossbred and 25 were indigenous. Results showed that the average daily milk production of Local, Shahiwal x Local, Friesian x Local and Jersey x Local dairy cows was 2.26±0.19, 4.9±0.95, 6.0±1.0 and 5.71±0.87 liter respectively. The average age of calving interval and lactation length of the crossbred and indigenous cows did not differ significantly (P>0.05). However, the average age at puberty of Shahiwal x Local, Friesian x Local and Jersey x Local was significantly (P